Angular‐split/temporal‐delay approach to ultrafast protein dynamics at XFELs. Issue 7 (5th July 2016) - Ren, Zhong; Yang, Xiaojing
Abstract : An angular‐split/temporal‐delay approach offers a solution to crystallographic observations of ultrafast structural dynamics in biological macromolecules. Abstract : X‐ray crystallography promises direct insights into electron‐density changes that lead to and arise from structural changes such as electron and proton transfer and the formation, rupture and isomerization of chemical bonds. The ultrashort pulses of hard X‐rays produced by free‐electron lasers present an exciting opportunity for capturing ultrafast structural events in biological macromolecules within femtoseconds after photoexcitation. However, shot‐to‐shot fluctuations, which are inherent to the very process of self‐amplified spontaneous emission (SASE) that generates the ultrashort X‐ray pulses, are a major source of noise that may conceal signals from structural changes. Here, a new approach is proposed to angularly split a single SASE pulse and to produce a temporal delay of picoseconds between the split pulses. These split pulses will allow the probing of two distinct states before and after photoexcitation triggered by a laser pulse between the split X‐ray pulses. The split pulses originate from a single SASE pulse and share many common properties; thus, noise arising from shot‐to‐shot fluctuations is self‐canceling. The unambiguous interpretation of ultrafast structural changes would require diffraction data at atomic resolution, as these changes may or may not involve any atomic displacement. This approach, in combination with the strategy of serial crystallography, offers a solution to study ultrafast dynamics of light‐initiated biochemical reactions or biological processes at atomic resolution.